2010
DOI: 10.1002/app.32621
|View full text |Cite
|
Sign up to set email alerts
|

Annealing and ultraviolet treatment of plasma fluorocarbon films for enhanced cohesion and stability

Abstract: Stents, commonly used for the treatment of cardiovascular diseases, are mainly made of 316L stainless steel. They are, however, prone to corrosion when they are in contact with human body fluid. To prevent this corrosion process and to ameliorate their patencies, in this study, we used a strategy to cover stent materials with a protective fluorocarbon layer deposited by plasma polymerization. In an approach to optimize its cohesion properties and stability, posttreatments, namely, thermal annealing and UV irra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Therefore, the etching induced a highly sensitive interface and water infiltration through nanopinholes in the coating led to a more important reoxidation. Nanopinholes have been evidenced by previous NEXAFS analyses . Moreover, Wambach et al showed that the oxidation rate of the stainless steel was about 10 times higher in water than in air, which could explain the fact that the oxide layer enlargement caused by aging exceeds the thickness of the native oxide layer.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Therefore, the etching induced a highly sensitive interface and water infiltration through nanopinholes in the coating led to a more important reoxidation. Nanopinholes have been evidenced by previous NEXAFS analyses . Moreover, Wambach et al showed that the oxidation rate of the stainless steel was about 10 times higher in water than in air, which could explain the fact that the oxide layer enlargement caused by aging exceeds the thickness of the native oxide layer.…”
Section: Resultsmentioning
confidence: 94%
“…In this context, CF x plasma deposition on SS316L has been investigated and previous results showed promising adhesion properties for the fluorocarbon films after a plastic deformation similar to a stent expansion. Previous characterizations by near-edge X-ray absorption fine structure (NEXAFS) showed the occurrence of nanodefects, which led to water diffusion during immersion in aqueous medium and resulted in chemical modifications and reorganization of the coating . To lower the nanodefects density, to promote the film growth and to increase the film stability, we applied different plasma etching sequences prior to the coating deposition.…”
Section: Introductionmentioning
confidence: 99%
“…The PTFE in the coating layer retained its powder shape due to water evaporation during the spin coating process and had a noticeably poor adhesion and durability. This outcome was expected because PTFE exhibits low adhesion with the substrate when coated using the spin coating method alone . Furthermore, the measurement of contact angle which has a strong dependency on macroscopic properties showed that the coatings were not hydrophobic, which is one of the properties and advantages of PTFE.…”
Section: Methodsmentioning
confidence: 93%
“…Furthermore, the measurement of contact angle which has a strong dependency on macroscopic properties showed that the coatings were not hydrophobic, which is one of the properties and advantages of PTFE. Since it is well accepted that macroscopic properties of multiphase composite materials depend on the interfacial bonding strength of the matrix and the reinforcing phase , the PTFE coatings prepared by the spin coating method needed to be subsequently processed through a post‐treatment method such as heat treatment to improve their integrity .…”
Section: Methodsmentioning
confidence: 99%
“…X-ray photoemission electron microscopy (X-PEEM) is used by many groups to study Bsoft[ surfaces, such as those associated with bio-adhesion phenomena and the structure of organic thin films [1][2][3]. X-PEEM can be used to extract near-edge x-ray absorption fine structure (NEXAFS) spectra of the near surface region of a sample ($5 nm deep [4]) with the high lateral spatial resolution of PEEM.…”
Section: Introductionmentioning
confidence: 99%